MeCP2 heterochromatin organization is modulated by arginine methylation and serine phosphorylation - Schmidt, Annika; Frei, Jana; Poetsch, Ansgar; Chittka, Alexandra; Zhang, Hui; Aßmann, Chris; Lehmkuhl, Anne; Bauer, Uta-Maria; Nuber, Ulrike A.; Cardoso, M. Cristina (Frontiers in Cell and Developmental Biology, 2022)
Rett syndrome is a human intellectual disability disorder that is associated with mutations in the X-linked MECP2 gene. The epigenetic reader MeCP2 binds to methylated cytosines on the DNA and regulates chromatin organization. We have shown previously that MECP2 Rett syndrome missense mutations are impaired in chromatin binding and heterochromatin reorganization. Here, we performed a proteomics analysis of post-translational modifications of MeCP2 isolated from adult mouse brain. We show that MeCP2 carries various post-translational modifications, among them phosphorylation on S80 and S421, which lead to minor changes in either heterochromatin binding kinetics or clustering. We found that MeCP2 is (di)methylated on several arginines and that this modification alters heterochromatin organization. Interestingly, we identified the Rett syndrome mutation site R106 as a dimethylation site. In addition, co-expression of protein arginine methyltransferases (PRMT)1 and PRMT6 lead to a decrease of heterochromatin clustering. Altogether, we identified and validated novel modifications of MeCP2 in the brain and show that these can modulate its ability to bind as well as reorganize heterochromatin, which may play a role in the pathology of Rett syndrome.